Evaluation of Bone–Implant Interface: Effects of Angiotensin II Receptor Blockade in Hypertensive Rats - Mulinari-Santos, Gabriel [UNESP] (2025)
Hypertension is a global health concern not only correlated with cardiovascular complications, but also with impaired bone metabolism, potentially affecting healing at the bone–implant interface. Losartan, an angiotensin II receptor blocker (ARB) commonly prescribed for hypertension, has shown beneficial effects on bone healing in spontaneously hypertensive rats (SHRs). However, the influence of hypertension and ARBs like losartan on the bone cellular response at the bone–implant interface remains underexplored. Methods: A total of 32 rats were included in this study: 16 SHRs, with 8 receiving losartan (30 mg/kg daily) and 8 receiving no treatment, and 16 normotensive Wistar rats, with 8 receiving losartan and 8 receiving no treatment. After one week of treatment, titanium implants were placed into the tibia of all the animals. The bone–implant interface was assessed 60 days post-implantation using micro-computed tomography (µCT) and an immunohistochemical analysis. Results: (i) The ARB treatment significantly increased the bone volume and bone–implant contact in the SHRs receiving losartan compared to the untreated SHRs. (ii) Consistent with the µCT findings, the immunohistochemistry further confirmed regular bone turnover and increased osteocalcin (OC) mineralization in the treated SHRs. In contrast, no alterations in the bone microarchitecture were noted in the Wistar rats treated with losartan. Conclusions: The results suggest that losartan, an ARB drug, improves bone volume and bone turnover at the bone–implant interface in SHRs.